Meaning Does Not Affect Consonant Discrimination Accuracy or Response Time in A Same-Different Segment Comparison Task (Caligrama: Revista de Estudos Românicos, 2024)
This article reports on three studies designed to test whether knowing the meaning of a word can influence the ability to discriminate sounds in it. In a samedifferent paradigm that required overt segmentation, we investigate the ability to compare consonants in the onset position of a pair of one-syllable pseudowords before (pre-test) and after (post-test) a training phase in which we attributed meanings to half of the pseudowords used. Reduced response time and increased accuracy (percentage of correct answers) in the post-tests revealed a training effect in two experiments. Still, there was no difference between pseudowords to which meanings were attributed or not. Conclusion: Knowing the meaning of a word does not influence the ability to discriminate sounds in it.